2003
DOI: 10.1099/jmm.0.05123-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of clinical and environmental isolates of vancomycin-resistant Enterococcus faecium and Enterococcus faecalis from a teaching hospital in Wales

Abstract: The present study describes the first molecular characterization of environmental and clinical isolates of vancomycin-resistant enterococci (VRE) in Wales. Over a 3-month period (May-July 2000), 134 isolates of VRE (89 Enterococcus faecium and 45 Enterococcus faecalis) were isolated from the patient environment of the University Hospital of Wales (UHW) in Cardiff, Wales, UK. In addition, over the same time-period, 24 clinical isolates of VRE (20 isolates of E. faecium and four isolates of E. faecalis) were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 21 publications
1
22
0
1
Order By: Relevance
“…Few studies, however, have used molecular typing to evaluate the environment as a source of VRE [28][29][30]. These studies only investigated the environment as a source of VRE outbreaks [28][29][30]. In the present study, the most frequent environmental sites and equipment contaminated by VRE were those near to the patients and frequently touched by the HCW, such as bedside shelves, sphygmomanometers, bed edge, and stethoscopes, as previously reported.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Few studies, however, have used molecular typing to evaluate the environment as a source of VRE [28][29][30]. These studies only investigated the environment as a source of VRE outbreaks [28][29][30]. In the present study, the most frequent environmental sites and equipment contaminated by VRE were those near to the patients and frequently touched by the HCW, such as bedside shelves, sphygmomanometers, bed edge, and stethoscopes, as previously reported.…”
Section: Discussionmentioning
confidence: 68%
“…Studies using multivariate analysis showed that placement in a contaminated room was associated with VRE acquisition (p = 0.020) [26], and that VRE-colonized room occupants within the previous 2 weeks and previous positive room culture remained independent predictors of VRE acquisition, after being adjusted for colonization pressure and antibiotic exposure [4]. Few studies, however, have used molecular typing to evaluate the environment as a source of VRE [28][29][30]. These studies only investigated the environment as a source of VRE outbreaks [28][29][30].…”
Section: Discussionmentioning
confidence: 91%
“…[13,14] Although we found 8.5%, 3% and 2% of isolates were resistant to vancomycin, teicoplanin and linezolid, respectively, diverse patterns of enterococci resistance have been reported from many countries. [13][14][15] In vitro resistance to linezolid is mediated via mutations in the central region of domain V of 23SrRNA and/ or by as yet unknown mechanisms. [7,6] However, resistance in wild-type isolates of Enterococcus and Staphylococcus is conferred by a single nucleotide transvertion at position 2576 in 23SrRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Such problems are particularly evident in hospitals, where they frequently present as nosocomial outbreaks. The most important nosocomial resistance today is caused by methicillin-resistant Staphylococcus aureus (MRSA) (1,2), vancomycinresistant enterococci (VRE) (3,4) and Enterobacteriaceae with extended-spectrum beta-lactamases (5,6). In addition, MRSA can also be resistant to aminoglycosides, often also to fluoroquinolones, and most other antibiotics (7,8).…”
mentioning
confidence: 99%
“…These multiresistant clones of S. aureus often occur as epidemic strains. Moreover, the VRE are also appearing as multiresistant strains which are often resistant to almost all antibiotics (3,4). These bacteria are mainly spread by person-to-person contact (9,10).…”
mentioning
confidence: 99%